(untitled) (Medical Forum Monthly, 2020)
Objective: To study the incidence/prevalence of Scabies in Sialkot. Study Design: Retrospective study Place and Duration of Study: This study was conducted at Idris Teaching Hospital Sialkot from Jan 2019 to December 2019. Materials and Methods: There were 2520 patients of scabies were included in this study Male 1297(51.46%) and female 1223 (48.51%), the history and family history were recorded. The examination was conducted on all the patients. The demographic bio data and incidence of patients of scabies from Jan-Dec 2019 were recorded. The written informed consent was taken before the study of patients. The permission of ethical committee was considered for collection of data and publishing it in medical journal. The data was analyzed on SPSS version 10 for results. Results: The incidence of scabies was the highest at the age of 5-15 years 621 (24.64%) of total patients. The incidence of scabies was the lowest at age below 5 years 100(3.96%). The incidence of scabies was the highest in lower class 1263(49.72%) and the incidence of scabies were lowest in high class 400(15.74%). The incidence of scabies was highest in rural area 1581(62.73%) and in urban area it was lowest 939(37.26%). The incidence of scabies was the highest in month of MAY-June 501 (19.88%) patients and lowest in the month of Jan-Feb 310 (12.30%) patients. Conclusion: It was concluded that the incidence of scabies was highest in the rural area and in the lower class at age of 5-15 years and highest in hot weather and lowest in cold weather.